2019
DOI: 10.1097/olq.0000000000001070
|View full text |Cite|
|
Sign up to set email alerts
|

High Prevalence of Sexually Transmitted Infections, and High-Risk Sexual Behaviors Among Indigenous Adolescents of the Comarca Ngäbe-Buglé, Panama

Abstract: Background There is scant information on sexually transmitted infection (STI) prevalence and risk factors among Latin American indigenous populations. We investigated STI prevalence and risk factors among adolescents of the Comarca Ngäbe-Buglé indigenous region of Panama. Methods A population-based cross-sectional study was conducted among school-going adolescents aged 14 to 19 years. Eligible consenting participants self-completed a questionnaire and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 14 publications
1
31
0
1
Order By: Relevance
“…Of them, just 53% were on antiretroviral therapy (ART). 4 In Panama, the HIV epidemic is affecting key populations, such as men who have sex with men, 5 low-income population, 6 youth, and adult population (15-50 years old) collectively, adding more than half of new HIV infections annually. 7 Still, people older than 50 years old are arriving to care with more HIV related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Of them, just 53% were on antiretroviral therapy (ART). 4 In Panama, the HIV epidemic is affecting key populations, such as men who have sex with men, 5 low-income population, 6 youth, and adult population (15-50 years old) collectively, adding more than half of new HIV infections annually. 7 Still, people older than 50 years old are arriving to care with more HIV related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV epidemic in the CNB is concentrated among young men and is influenced by lack of prevention in male same-sex relationships. Local epidemiological surveys indicate that men who have sex with men also have sex with women (Gabster et al 2019). We found strong beliefs that condoms are primarily used to prevent pregnancy, and therefore not needed within same-sex relationships.…”
Section: Discussionmentioning
confidence: 67%
“…Prevalence of HIV in the CNB is 2%, twice the national average, with most infections found among young-adult young men (Ministerio de Salud 2018). Among young people 14-19 years old in CNB, prevalence of other STIs have been found to vary between sexes, where active syphilis has been found to be more prevalent in males, however genital chlamydia infections are more common among young women (Gabster A et al 2019). A recent nationwide sexual and reproductive health survey found that among young people of CNB, 26.1% of young women and 26.5% of young men reported to have engaged in sexual relations before the age of 15; among 15-24 year-olds, 4.8% of young women and 0.6% of young men reported having used a condom at sexual debut; and finally 81.2% adult and young women in the CNB report they cannot deny sexual relations with their partner (De León et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Panama had an estimated HIV prevalence of 0.6%, described as a concentrated epidemic among men who have sex with men (MSM) (6.9%) and transwomen (29.6%) populations [15]. Correspondingly, high STI prevalence has been found among MSM, female sex workers, and adolescents [16-19]. During COVID-19 measures, access to key services was interrupted, with over 50% of those needing a STI or HIV testing not getting it.…”
Section: Discussionmentioning
confidence: 99%